2021
DOI: 10.3390/antibiotics10030264
|View full text |Cite
|
Sign up to set email alerts
|

Potential Target Site for Inhibitors in MLSB Antibiotic Resistance

Abstract: Macrolide–lincosamide–streptogramin B antibiotic resistance occurs through the action of erythromycin ribosome methylation (Erm) family proteins, causing problems due to their prevalence and high minimal inhibitory concentration, and feasibilities have been sought to develop inhibitors. Erms exhibit high conservation next to the N-terminal end region (NTER) as in ErmS, 64SQNF67. Side chains of homologous S, Q and F in ErmC’ are surface-exposed, located closely together and exhibit intrinsic flexibility; these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Molecular modeling studies showed that quinine, ketoprofen, and fosfomycin formed H -bond and hydrophobic interactions with key amino acids at the SAM-binding site of the ErmC’ protein ( Table S7 ). This binding inhibits N -6 methylation of A2058 at the macrolides-binding site of 23S rRNA in 50S ribosomal subunit, thus allowing clindamycin to bind to its binding site on the ribosome and decreasing inducible clindamycin resistance [ 90 ]. In brief, quinine achieved the highest binding affinity, indicating that quinine had the highest inhibitory activity on inducible clindamycin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular modeling studies showed that quinine, ketoprofen, and fosfomycin formed H -bond and hydrophobic interactions with key amino acids at the SAM-binding site of the ErmC’ protein ( Table S7 ). This binding inhibits N -6 methylation of A2058 at the macrolides-binding site of 23S rRNA in 50S ribosomal subunit, thus allowing clindamycin to bind to its binding site on the ribosome and decreasing inducible clindamycin resistance [ 90 ]. In brief, quinine achieved the highest binding affinity, indicating that quinine had the highest inhibitory activity on inducible clindamycin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the NdeI site could be found in ermK structural gene and site directed mutagenesis of the ermK gene without any amino acid change ( G C A TATG TG , which code 158AYV160 but as could be seen in underlined letters, it contains NdeI recognition site, so it changed to C T TATG as denoted in italicized letter.) was carried out using a sequential PCR method, known as the “splicing by overlap extension” ( 31 , 32 ). In brief, to obtain the DNA fragment encompassing the 5′ end region, including the mutagenizing site, PCR was carried out using Bacillus halodurans C-125 chromosomal DNA as a template and the oligonucleotides oligo-1 and oligo-2 ( Table 2 ) as the forward and reverse primers.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of each Erm protein expressed in E. coli was evaluated as described in the previous report with slight modifications ( 32 ). Briefly, each E. coli culture ( E. coli HJJ402, E. coli HJJ502, and E. coli HJJ602) was spread on quartered LB agar plate.…”
Section: Methodsmentioning
confidence: 99%
“…The protein MLS_B (also known as ERM_B) was predicted using the artificial intelligence program AlphaFold. Following the studies by Lee et al, 44 the N-terminal portion (NTERM) was identified as the region primary interest for the activities of proteins encoded by ERMs. The following approach was used to construct the spatial grid box the region of interest was identified between amino acids 8TQNF11, delimited within the region defined as the X-motif.…”
Section: -(34-dihydroxyphenyl)-8-(3-fluoroanilino)-357-trihydroxy-4h−...mentioning
confidence: 99%